2012
DOI: 10.1093/ejcts/ezr133
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of post-thoracotomy pain: a comparison between total intravenous anaesthesia and inhalation anaesthesia

Abstract: TIVA with propofol and remifentanil may reduce the incidence of CPTS at 3 and 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 22 publications
1
35
2
1
Order By: Relevance
“…A total of nine trials reported pain intensity at or around 24 h postsurgery, in which 595 patients received propofol anaesthesia, while 586 had inhalational anaesthesia [10,11,18,19,21,22,25,28,29]. Overall, compared with inhalational anaesthetics, patients who received propofol reported significantly lower pain scores 24 h postsurgery (Hedge's g (95% CI) À0.134 (À0.248 to À0.021) (p = 0.021) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of nine trials reported pain intensity at or around 24 h postsurgery, in which 595 patients received propofol anaesthesia, while 586 had inhalational anaesthesia [10,11,18,19,21,22,25,28,29]. Overall, compared with inhalational anaesthetics, patients who received propofol reported significantly lower pain scores 24 h postsurgery (Hedge's g (95% CI) À0.134 (À0.248 to À0.021) (p = 0.021) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies which reported 2-h or 24-h pain scores, only three investigated morphine-equivalent consumption at or around 24 h postsurgery [18,21,29]. A total of 248 patients received propofol, and 248 patients received inhalational anaesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The use of nitrous oxide has been shown to decrease the risk of chronic postsurgical pain after major noncardiac surgery, 19 and total intravenous anesthesia with propofol and remifentanil may reduce the incidence of chronic postsurgical pain after thoracotomy when compared with inhalation anesthesia. 20 This is an area of anesthesiology that requires further study.…”
Section: Does the Type Of Anesthesia Matter?mentioning
confidence: 99%
“…18 Il a été démontré que l'utilisation de protoxyde d'azote réduisait le risque de douleur chronique postchirurgicale après une chirurgie non cardiaque majeure, et l'anesthésie intraveineuse totale réalisée avec du propofol et du rémifentanil pourrait réduire l'incidence de douleur chronique postchirurgicale après une thoracotomie comparativement à une anesthésie par inhalation. 20 Ce domaine de l'anesthésiologie nécessite des études supplémentaires.…”
Section: Le Rôle De L'analgésie Multimodaleunclassified